Determination of cuticular and internal fatty acids of Chorthippus brunneus males and females using HPLC‐LLSD and GC–MS. (17th February 2016) - Gołębiowski, Marek; Cerkowniak, Magdalena; Ostachowska, Aleksandra; Boguś, Mieczysława I.; Stepnowski, Piotr
Abstract: Insects are of growing significance in veterinary medicine and human healthcare; therefore, an understanding of their biology is very important. The cuticular and internal fatty acid compositions of Chorthippus brunneus males and females have been studied for the first time. The lipids of males and females were separated into classes of compounds using high‐performance liquid chromatography with a laser light scattering detector. The free fatty acid (FFA) fractions obtained by HPLC were silylated and then analyzed by GC–MS. The cuticular lipids of males contained 15 saturated, four unsaturated with even‐numbered and two unsaturated with odd‐numbered carbon chains, FFAs ranging from C8 to C25. The major free fatty acids in males were C16 (20.8%), C18:2 (8.5%), C18:1 (32.9%) and C18 (24.4%). The cuticular lipids of females contained 17 saturated, four monounsaturated and two diunsaturated free fatty acids ranging from C8 to C30. The major cuticular fatty acids in females were C16 (25.1%), C18:2 (6.2%), C18:1 (23.7%) and C18:0 (33.2%). The internal FFAs of males consisted of 20 compounds ranging from C8 to C26. Four of these compounds were detected as major compounds: C16 (14.1%), C18:2 (21.6%), C18:1 (38.0%) and C18 (22.5%). Among 18 internal free fatty acids of females, C16 (22.3%), C18:2 (10.9%), C18:1 (40.2%) and C18 (20.5%) were the most abundant compounds. The following cuticular fatty acids present in the lipids of females were absent in the lipids of males: C26, C27 and C30. On the other hand, only C24 was absent from the cuticular lipids of females. Only C10 and C24 internal fatty acids present in the lipids of males were absent in the lipids of females. Copyright © 2016 John Wiley & Sons, Ltd.